The Remarkable Antioxidant and Anti-Inflammatory Potential of the Extracts of the Brown Alga Cystoseira amentacea var. stricta - Gina De La Fuente; Marco Fontana; Valentina Asnaghi; Mariachiara Chiantore; Serena Mirata; Annalisa Salis; Gianluca Damonte; Sonia Scarfì (Marine Drugs, 2020)
Inflammation and oxidative stress are part of the complex biological responses of body tissues to harmful stimuli. In recent years, due to the increased understanding that oxidative stress is implicated in several diseases, pharmaceutical industries have invested in the research and development of new antioxidant compounds, especially from marine environment sources. Marine seaweeds have shown the presence of many bioactive secondary metabolites, with great potentialities from both the nutraceutical and the biomedical point of view. In this study, 50%-ethanolic and DMSO extracts from the species C. amentacea var. stricta were obtained for the first time from seaweeds collected in the Ligurian Sea (north-western Mediterranean). The bioactive properties of these extracts were then investigated, in terms of quantification of specific antioxidant activities by relevant ROS scavenging spectrophotometric tests, and of anti-inflammatory properties in LPS-stimulated macrophages by evaluation of inhibition of inflammatory cytokines and mediators. The data obtained in this study demonstrate a strong anti-inflammatory effect of both C. amentacea extracts (DMSO and ethanolic). The extracts showed a very low grade of toxicity on RAW 264.7 macrophages and L929 fibroblasts and a plethora of antioxidant and anti-inflammatory effects that were for the first time thoroughly investigated. The two extracts were able to scavenge OH and NO radicals (OH EC50 between 392 and 454 μg/mL; NO EC50 between 546 and 1293 μg/mL), to partially rescue H2O2-induced RAW 264.7 macrophages cell death, to abate intracellular ROS production in H2O2-stimulated macrophages and fibroblasts and to strongly inhibit LPS-induced inflammatory mediators, such as NO production and IL-1α, IL-6, cyclooxygenase-2 and inducible NO synthase gene expression in RAW 264.7 macrophages. These results pave the way, for the future use of C. amentacea metabolites, as an example, as antioxidant food additives in antiaging formulations as well as in cosmetic lenitive lotions for inflamed and/or damaged skin.